Becoming Traviata - Béziat, Philippe 1963-; Dessay, Natalie 1965-; Langrée, Louis 1961- (Axiom Films, 2012)
Bonus: Interviews mit J.-F. Sivadier, N. Dessay, L. Langrée, C. Castronove. L. Tézier u. P. Béziat